(3eYQaI GdUMGHIs - (3nCoHh ofnYje CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj,J (B430 (3g` s
(3ChdgG (B:s
(3jHJOF HYHO Gddg Hf NHjH s
(3BNQgG (B:s
(3hjfJgi Edi BNQ GdcJGH s
(3YdjgG SeGY eDQN SfI (B551(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B151 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(497) s
Keywords: (3GdJGQjNs